Learning Difficulties in Biochemistry: Student Perspectives and Emerging Trends - Sa'adah, Siti Imroatus; Mamluaturrahmatika, Annisa; Marpaung, Aisyatur Radhwa; Arianingrum, Retno; Atun, Sri; Naqsyahbandi, Fajar (Jurnal Tadris Kimiya, 2025)
This study analyzes students’ learning difficulties in understanding biochemistry concepts, materials, and processes through a survey, and examines bibliometric patterns of biochemistry learning models and methods to identify potential alternative solutions. A descriptive research design was employed, combining survey methods and bibliometric analysis. The survey was conducted with 82 fourth-semester students of the Chemistry Study Program, including Class B (48 students) and Class E (34 students). Data were collected using an open-ended questionnaire and analyzed descriptively and qualitatively. In parallel, a bibliometric analysis of scientific articles on biochemistry learning difficulties was performed using VOSviewer software, identifying dominant sub-themes such as learning models, learning methods, and biochemistry education. The survey results indicate that students experience the greatest difficulties in protein biosynthesis (82%), lipid metabolism (55%), enzymes (53%), protein metabolism (50%), and carbohydrate metabolism (45%). These findings highlight challenges with metabolic pathways and molecular structures, emphasizing the need for visualization-based learning media. Additionally, the bibliometric analysis suggests that flipped classroom and blended learning approaches have strong potential as innovative strategies to address these difficulties. The study concludes with recommendations for future research focused on the development and evaluation of such approaches in biochemistry education.